A typology of heritage crime victims - Poyser, Bethan (Critical criminology, 2022)
Heritage crime has to date received little criminological interest relative to other topics within the discipline. Therefore, the current literature on the area is limited. Victims of heritage crime are significantly under-represented in the current body of literature, and empirical research on heritage crime and victimisation is lacking; as is any theoretical development of the phenomenon. This article makes small steps towards addressing some of the substantial gaps relating to heritage crime victimisation in presenting the first typology of heritage crime victims. This typology is the result of research conducted across England and Wales with a sample of heritage practitioners, police officers, and heritage crime victims. Based on the research conducted, we hope to contribute towards the body of police and heritage practitioner knowledge concerning victims of heritage crime. The typology may, with further research, be applied or adapted to include heritage crime victims across the globe.